The intraoperative frozen section analysis of thyroid nodules categorized under Bethesda III-IV-V, accompanied by concurrent imprint cytology as a diagnostic technique (Annals of Medical Research, 2023)
Aim: Addressing therapeutic challenges posed by thyroid nodules classified under Bethesda categories III-IV-V is a primary concern. The aim of this study is to evaluate the diagnostic outcomes of intraoperative frozen section (IFS) when applied to these specific thyroid nodules, alongside evaluating the diagnostic performance of IFS when used in conjunction with concurrent imprint cytology (IC).Materials and Methods: We conducted a comprehensive search in the electronic hospital database to retrieve IFS results and final diagnosis of cases with category III-IV-V thyroid nodules. These patients had undergone nodule resection or partial thyroidectomy with IFS. We gathered information regarding patient demographics, nodule dimensions, and the execution of concurrent IC.Results: Our study comprised 81 eligible patients. Female/male ratio was 3.2. Mean patient age was 43.5 years. Average nodule size was 21.7 mm. IC was conducted in 20 cases as part of the IFS procedure. Sensitivity and specificity of IFS were 71% and 95%, respectively. Positive predictive value (PPV) was 83% and negative predictive value (NPV) was 90%. Diagnostic accuracy of IFS was 88%. We stratified cases into those with and without IC. IFS with IC exhibited a sensitivity, specificity, PPV, NPV of 80%, 93%, 80%, 93%, respectively. In contrast, IFS without IC had sensitivity, specificity, PPV, NPV values of 68%, 95%, 83%, 90%, respectively.Conclusion: Inconsistent pathological assessments and varying malignancy rates present challenges when managing Bethesda category III-IV-V thyroid nodules. In addressing these challenges, IFS emerges as a potential effective method. Nonetheless, IFS exhibits restricted sensitivity in detecting malignancies within Bethesda category III-IV-V nodules. Inclusion of concurrent IC has the potential to improve the precision of IFS in identifying malignancies. A more extensive study in this regard is warranted.